Hybrid FDG-PET/MR imaging of chronic osteomyelitis: a prospective case series - Hulsen, Dennis Jan Willem (Eur J Hybrid Imaging, 2019)
BACKGROUND: Magnetic resonance imaging (MRI) and 2-[18F]-fluoro-2-deoxy-D-glucose (FDG) positron emission tomography paired with computed tomography (PET/CT) are two commonly used imaging modalities in the complicated diagnostic workup of osteomyelitis. Diagnosis using these modalities relies on, respectively, anatomical (MRI) and metabolic (PET) signs. With hybrid PET/MRI being recently available, our goal is to qualitatively compare hybrid FDG PET/MRI to FDG PET/CT in the diagnosis and operative planning of chronic osteomyelitis. METHODS: Five patients with suspected chronic osteomyelitis in an extremity underwent an (18)F-FDG single-injection/dual-imaging protocol with hybrid PET/CT and hybrid PET/MR. Images and clinical features were evaluated using a standardized assessment method. Standardized uptake value (SUV) measurements were performed on all images. Concordant and discordant findings between PET/MRI and PET/CT were analysed. RESULTS: The consensus diagnoses based on PET/MRI and PET/CT images were identical for all five patients. One discrepancy between PET/MRI and PET/CT was found in the assessment of the features in one patient. PET signal intensities and target-to-background ratios were on average highest for PET/MRI. On PET/MRI, the location of infection based on FDG uptake could clearly be correlated with certain soft tissue structures (oedema, fluid collection, or muscle), which is paramount for surgical planning. CONCLUSIONS: In the presented cases, FDG PET/MRI led to the same diagnosis and provided at least the same diagnostic information as PET/CT. PET/MRI was able to provide additional soft-tissue information for the physician planning treatment. Because of this, we suggest that PET/MRI could be used for osteomyelitis diagnosis and treatment planning.